Beyond basic resuscitation: What are the next steps to improve the outcomes of resuscitation at birth when resources are limited?. Issue 5 (October 2018) - Niermeyer, Susan; Robertson, Nicola J.; Ersdal, Hege L.
Abstract: Implementation of basic neonatal resuscitation in low- and middle-income settings consistently saves lives on the day of birth. What can be done to extend these gains and further improve the outcomes of infants who require resuscitation at birth when resources are limited? This review considers how resuscitation and post-resuscitation care can advance to help meet the survival goals of the Every Newborn Action Plan for 2030. A brief summary of the evidence for benefit from basic neonatal resuscitation training in low- and middle-income countries highlights key aspects of training, low-dose high-frequency practice, and implementation with single providers or teams. Reorganization of processes of care, as well as new equipment for training and selected clinical interventions can support further quality improvement in resuscitation. Consideration of the resuscitation algorithm itself focuses on important actions for all babies and special considerations for small babies and those not crying after thorough drying. Finally, an examination of the vital elements of assessment and continued stabilization/care in the health facility draws attention to the opportunities for prevention of intrapartum-related events and the gaps that still exist in postnatal care. Extending and improving implementation of basic resuscitation to make it available to all newborns will assure continued benefit to the largest numbers; once high coverage and quality of basic resuscitation are achieved, health systems with maturing capacity can extend survival gains with improved prevention, more advanced resuscitative interventions, and strengthened postnatal care.